EVALUASI GERAKAN MORAL BERSIH DALAM IMPLEMENTASI GCG DI KEDAI ES KRIM AICE MASJID ZAYED SOLO - Nany, Magdalena; Yonivianta, Samuel Jordan; Tobu, Oktapianus Geofani Bulu Bepa; Subroto, Asto Sunu; Kuntadi, Yahya Agung (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
Effective governance is fundamental to a company's long-term success and growth. A crucial initial step for companies is to establish a clear organizational structure in implementing Good Corporate Governance (GCG) is through the Clean, Transparent, and Professional (BTP) Moral Movement. As a newly established franchise business, the manager of the Aice Masjid Zayed Solo ice cream shop needs to get used to the implementation of a clean moral movement that contains the values of integrity, credibility, honesty and anti-corruption. The data were gathered through interviews and observations. Store managers have shown a high commitment to implementing the clean moral movement, although there has been no regular training on ethics and integrity for employees and there has been no clear written policy on the prohibition of corruption, collusion, and nepotism